Indonesian Government’s Efforts to Cooperate with Malaysia’s Government in Protecting Educational Rights of Indonesian Migrant Workers Children (Case Study: Children of Indonesian Migrant Workers in Sabah) - Yuvanti, Dita Aprilia (Journal of ASEAN Dynamics and Beyond, 2021)
Indonesia and Malaysia are geographically close countries. That is one of the reason why many Indonesian Migrant Workers come to Malaysia to look for a job. Although Malaysian Immigration Agency has banned migrants from bringing their families with them, there are still 50.000 Indonesian children in Sabah who work with their parents. But these children do not get a proper education. This study aims to examine how Indonesian Government response and effort to fulfill the protection of the education rights of Indonesian migrant children in Sabah, Malaysia. Using the concept of Soft Power Diplomacy and Legal Protection for Children, this study concludes that the Indonesian government has sought legal protection and education for Indonesian children in Sabah from discrimination by establishing diplomatic relations with Malaysia, NGO Humana Child Aid Society, Kota Kinabalu Indonesian School, and the Community Learning Center.